Optimalisasi Marketplace Sebagai Strategi Efektif Untuk Perluasan Jaringan Pemasaran Kopi Ratu Produksi UMKM. Azka Food - Elok Novita Sari; Nur Faizin; Huda Ahmad Hudori (Indonesian Journal Publisher, 2025)
Azka Food is one of the UMKM that produce coffee products, located in Klungkung Village, Jember Regency. The capacity of coffee bean produced by Azka Food are quite large, which is around 20 tons in one harvest. However, Azka Food's partners are still constrained in product marketing. Where, the marketing system carried out by Azka Food still uses the Word of Mouth Marketing (WoMM) method. The disadvantage of this method is that the process of spreading and marketing products is very slow. So that to overcome this problem, the solution provided by the Team is the introduction and implementation marketing based on marketplace. The implementation method in this activity begins with a discussion to map the needs of partners. Then, Azka Food as partners are given an introduction and assistance regarding the online marketing system. The online marketing introduced to partners is marketing based on marketplace. Partners are given an introduction to several platforms that are commonly used in the marketplace. As a result of this service activity, partners have 2 accounts on 2 selected platforms, namely Shopee and Tokopedia. Partners are also given an introduction to how to manage an online store, starting from the preparation of uploaded products to the management of the transaction system. With the use of marketing through e-commerce, it will increase marketing cost efficiency by up to 35%. This figure is measured based on the calculation of total costs, which are carried out through e-commerce and conventional methods. Where online marketing will reduce the operational costs of conventional marketing, such as print advertising or physical distribution. Online marketing will make it easier for partners to monitor through transaction data which includes sales volume and the amount of turnover received. In addition, the reach of marketing areas and customers will be wider without any additional operational costs.